Charitable Trusts and Advancement of Religion: On a Whim and a Prayer? - Chevalier-Watts, Juliet (Victoria University of Wellington Law Review, 2012)
The advancement of religion is a controversial head of charitable trusts: whilst its foundations are based on tenets of intangible belief systems, New Zealand law, alongside other common law jurisdictions, supports the notion that the public benefit requirement of all charitable trusts be presumed in this particular head. Common law also reflects decades of evolution of the interpretation of the advancement of religion, thus not limiting the advancement of religion to only the traditional methods of yesteryear, such as offering church services. Nevertheless, with the recent contentious judgment in the New Zealand case of Liberty Trust v Charities Commission, this article submits that the established doctrines associated with the advancement of religion have been advanced beyond envisioned boundaries. The article supports a more conservative interpretation based on established case law. This would not only continue to support fully the evolution of the advancement of religion, but would also provide judicial certainty in an area of law that is undergoing continued change.